Legal Gaps in the Protection of Female Workers in the Informal Sector Based on Digital Platforms as a Basis for Reforming Labor Law in Indonesia - Wardatul Asriah; Azis Budianto (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze the legal gaps in regulating the status and protection of female workers in the informal digital platform-based sector and to formulate a direction for gender-sensitive labor law reform in Indonesia. The research method used is normative juridical with a statutory and conceptual approach, through an analysis of various regulations related to employment, women's protection, and social security. The results of the study indicate that there is a legal gap due to the non-recognition of platform workers as legal subjects in employment relations, so that female workers do not receive normative protections such as social security, maternity protection, wage certainty, and protection from digital-based violence. This condition has legal implications in the form of legal uncertainty, hidden exploitation, and strengthening gender inequality in the digital workplace. Therefore, it is necessary to reconstruct labor law that is adaptive to the development of the digital economy by integrating the principles of gender-responsive law, through recognizing the status of platform workers, expanding access to social protection, and strengthening regulations for the protection of female workers comprehensively to realize substantive justice.